Estimating the yield stability of heat-tolerant rice genotypes under various heat conditions across reproductive stages: a 5-year case study - Chao Wu (Nature Portfolio, 2021)
Abstract Heat events during the reproductive stages of rice plants induce great yield losses. Cultivating heat-tolerant varieties is a promising strategy for guaranteeing grain security under global warming scenarios. Most heat-tolerant rice genotypes were identified under heat during the flowering stage, but it is unclear whether these currently screened heat-tolerant rice genotypes maintain stable high grain yields when heat stress occurs during the other reproductive stages. In the present study, two notable heat-tolerant rice cultivars, Nagina22 and Shanyou63, and one typical heat-sensitive cultivar, Liangyoupeijiu, were evaluated for their yield response and yield stability under heat treatments during the panicle initiation, flowering, and grain filling stages during 2010–2014. Our results revealed that rice cultivars respond differently to heat stress during different reproductive stages. Nagina22 was the most tolerant to heat stress during the flowering and grain filling stages but was susceptible during panicle initiation; Shanyou63 was the most tolerant to heat stress during panicle initiation and grain filling and was moderately tolerant to heat stress during the flowering stages. Genotype and genotype-by-environment interaction biplot yield analysis revealed that Shanyou63 exhibited the highest stability in high grain yield, followed by Nagina22, and Liangyoupeijiu exhibited stable low grain yield when experiencing heat stress across the three reproductive stages. Our results indicate that the heat tolerance of different rice cultivars depends on the reproductive stage during which heat stress occurs, and the effects manifest as reductions in grain yields and seed setting rates. Future efforts to develop heat-tolerant varieties should strive to breed varieties that are comprehensively tolerant to heat stress during any reproductive stage to cope with the unpredictable occurrence of future heat events.